Transmigration across activated endothelium induces transcriptional changes, inhibits apoptosis, and decreases antimicrobial protein expression in human monocytes - Williams, Marcie R. (The Society for Leukocyte Biology, 2009)
We investigated the hypothesis that transmigration drives monocyte transcriptional changes. Using Agilent whole human genome microarrays, we identified over 692 differentially expressed genes (2×, P<0.05) in freshly isolated human monocytes following 1.5 h of transmigration across IL-1β-stimulated ECs compared with untreated monocytes. Genes up-regulated by monocyte transmigration belong to a number of over-represented functional groups including immune response and inhibition of apoptosis. qRT-PCR confirmed increased expression of MCP-1 and -3 and of NAIP following monocyte transmigration. Additionally, quantification of Annexin V binding revealed a reduction in apoptosis following monocyte transmigration. Comparison of gene expression in transmigrated monocytes with additional controls (monocytes that failed to transmigrate and monocytes incubated beneath stimulated ECs) revealed 89 differentially expressed genes, which were controlled by the process of diapedesis. Functional annotation of these genes showed down-regulation of antimicrobial genes (e.g., α-defensin down 50×, cathelicidin down 9×, and CTSG down 3×). qRT-PCR confirmed down-regulation of these genes. Immunoblots confirmed that monocyte diapedesis down-regulates α-defensin protein expression. However, transmigrated monocytes were functional and retained intact cytokine and chemokine release upon TLR ligand exposure. Overall, these data indicate that the process of monocyte transmigration across stimulated ECs promotes further monocyte recruitment and inhibits monocyte apoptosis. Unexpectedly, following transmigration, monocytes displayed reduced antimicrobial protein expression.